How are Long-Covid, Post-Sepsis-Syndrome and Post-Intensive-Care-Syndrome related? A conceptional approach based on the current research literature - Fleischmann-Struzek, Carolin; Joost, Franka E. A.; Pletz, Mathias W.; Weiß, Björn; Paul, Nicolas; Ely, E. Wesley; Reinhart, Konrad; Rose, Norman (Critical care (London, England), 2024)
Long-Covid (LC), Post-Sepsis-Syndrome (PSS) and Post-Intensive-Care-Syndrome (PICS) show remarkable overlaps in their clinical presentation. Nevertheless, it is unclear if they are distinct syndromes, which may co-occur in the same patient, or if they are three different labels to describe similar symptoms, assigned on the basis on patient history and professional perspective of the treating physician. Therefore, we reviewed the current literature on the relation between LC, PSS and PICS. To date, the three syndromes cannot reliably be distinguished due similarities in clinical presentation as they share the cognitive, psychological and physical impairments with only different probabilities of occurrence and a heterogeneity in individual expression. The diagnosis is furthermore hindered by a lack of specific diagnostic tools. It can be concluded that survivors after COVID-19 sepsis likely have more frequent and more severe consequences than patients with milder COVID-19 courses, and that are some COVID-19-specific sequelae, e.g. an increased risk for venous thromboembolism in the 30 days after the acute disease, which occur less often after sepsis of other causes. Patients may profit from leveraging synergies from PICS, PSS and LC treatment as well as from experiences gained from infection-associated chronic conditions in general. Disentangling molecular pathomechanisms may enable future targeted therapies that go beyond symptomatic treatment.